Treatment barriers among young adults living with a substance use disorder in Tshwane, South Africa - Tichaenzana Nyashanu; Maretha Visser (BMC, 2022)
Abstract Background Despite increasing substance use globally, substance use treatment utilisation remains low. This study sought to explore and measure substance use treatment barriers among young adults in South Africa. Methods The study was done in collaboration with the Community-Oriented Substance Use Programme run in Tshwane, South Africa. A mixed methods approach employing focus group discussions with key informants (n = 15), a survey with a random sample of people using substances and receiving treatment (n = 206), and individual semi-structured interviews (n = 15) was used. Descriptive statistics and thematic analysis were used to analyse data. Results Contextual barriers seemed more prominent than attitudinal barriers in the South African context. Fragmented services, stigma-related factors, an information gap and lack of resources and support (contextual factors), perceived lack of treatment efficacy, privacy concerns, and denial and unreadiness to give up (attitudinal factors) were treatment barriers that emerged as themes in both quantitative and qualitative data. Culture and religion/spirituality emerged as an important barrier/facilitator theme in the qualitative data. Conclusion Interventions need to embrace contextual factors such as culture, and more resources should be channelled towards substance use treatment. Multi-level stakeholder engagement is needed to minimise stigmatising behaviours from the community and to raise awareness of available treatment services. There is a need for strategies to integrate cultural factors, such as religion/spirituality and traditional healing, into treatment processes so that they complementarily work together with pharmacological treatments to improve health outcomes.